National paradigms in decentralized development: Evaluating bottom-up resilience strategies for achieving sustainable development goals - Muhammad Ihsan Darmawan (Journal of National Paradigm-Based Resilience Strategy, 2026)
Background: Achieving the Sustainable Development Goals (SDGs) leaves a significant exploration space in the context of regional autonomy development. With less than 5 years remaining towards the target, regional autonomy, especially in the smallest villages, continues to be encouraged as a space for creating sustainable development that starts from the bottom. Through official state regulations in laws and ministerial regulations as well as Village Medium-Term Development Plan/Rencana Pembangunan Jangka Menengah Desa (RPJMDes), a development model that looks participatory and inclusive has become a reference, but cannot be separated from several restrictions that make the need for a review of the inclusiveness of the model. Methods: This study uses a descriptive-qualitative method through a systematic review of policy documents and scientific literature. The data processing involved three systematic stages: reduction, categorization, and interpretation to synthesize the political implications of decentralized development in achieving SDGs under the framework of regional autonomy in Indonesia. Findings: The findings indicate that there are still significant challenges in establishing a truly participatory development model, despite indications that Indonesia already possesses sufficient institutional and political capacity to implement bottom-up approaches in development programs/policies. Furthermore, the analysis reveals that deeply rooted institutional and social cultures continue to hinder the shift from technocratic to participatory views, resulting in a decentralization process that remains partially democratic and often pseudo-participatory. Conclusion: This study concludes that development in Indonesia is not merely a technocratic-administrative matter, but rather a political process fraught with negotiations of interests. Novelty/Originality of this article: The novelty of this research lies in its critique of the traditional dichotomy between top-down and bottom-up approaches in the context of regional autonomy in Indonesia.